(untitled) (Revista de Ciências Agroveterinárias, 2011)
The objective of this work was to compare the analytical methodologies USEPA 3050 B, Tedesco (H2SO4 + H2O2) and Aqua Regia in the opening of samples of soils for the determination of the contents of Cd, Cu and Zn in soils collected at places without intentional antropic contamination. Samples of the superficial horizon of three soils of the East Mountain were used (PVA(m), PVA(g) and ADP) and three soils of the West (MT, NV and LB) of the State of Santa Catarina, Brazil. The quantification of the contents of Cd, Cu and Zn was accomplished through spectrum photometry of atomic absorption with atomization for fire. The methods differed significantly, and, the method USEPA 3050 B was capable to extract the largest amounts of Cd, As and Zn of the derived soils of mafic rocks appraised in this work.